2022
DOI: 10.1007/s10653-022-01415-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace element contamination in rice and its potential health risks to consumers in North-Central Vietnam

Abstract: This study assessed the potential health risks of ve elements (Ni, Cr, As, Cd, and Pb) in rice collected from three provinces in North-Central Vietnam, Thanh Hoa, Nghe An, and Ha Tinh. These provinces comprise areas with and/or without mining and industrial activities, focusing on two local population groups (adults and children under ve years old). Trace elements were determined by an inductively coupled plasma mass spectrometry (ICP-MS). The potential health risks were evaluated for different age groups usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Moreover, chromium and other heavy metals are classified as potent Group I carcinogens and cause various types of cancer in humans [42]. Previous studies in children have observed this over-ingestion of chromium associated with the consumption of rice [43], which is often included in baby food as a complementary ingredient to the usual protein sources. Table 4.…”
Section: Dietary Intake and Risk Assessmentmentioning
confidence: 99%
“…Moreover, chromium and other heavy metals are classified as potent Group I carcinogens and cause various types of cancer in humans [42]. Previous studies in children have observed this over-ingestion of chromium associated with the consumption of rice [43], which is often included in baby food as a complementary ingredient to the usual protein sources. Table 4.…”
Section: Dietary Intake and Risk Assessmentmentioning
confidence: 99%